2022
DOI: 10.3390/ani12070806
|View full text |Cite
|
Sign up to set email alerts
|

All-You-Can-Eat: Influence of Proximity to Maize Gardens on the Wild Diet and the Forest Activities of the Sebitoli Chimpanzee Community in Kibale National Park

Abstract: Frugivorous primates have developed several strategies to deal with wild fruit scarcity, such as modifying their activity budget or enlarging their diet. Agricultural expansion threatens primate habitats and populations (e.g., disease transmission, agrochemical exposure), but it also increases crop feeding opportunities. We aimed at understanding whether maize presence close to the natural habitat of chimpanzees, a threatened species, would lead to significant behavioral modifications. We monitored 20 chimpanz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 120 publications
(159 reference statements)
1
4
0
Order By: Relevance
“…Both isoprostanes and lipid peroxides (markers of oxidative damage to lipids) did not differ among the three exposure levels, indicating that lipid peroxidation was not affected by the differences in the diet. The current results confirmed that feeding on maize does not make a significant difference in the caloric intake for Sebitoli chimpanzees sampled as previously shown (Couturier et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Both isoprostanes and lipid peroxides (markers of oxidative damage to lipids) did not differ among the three exposure levels, indicating that lipid peroxidation was not affected by the differences in the diet. The current results confirmed that feeding on maize does not make a significant difference in the caloric intake for Sebitoli chimpanzees sampled as previously shown (Couturier et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…We used this as proxy for their pesticide exposure level as high, medium and low. To determine the category of exposure for a given individual, we used both the camera trap frequency of detection at the border between crops and the forest (Couturier et al 2022) and the long-term observations of the ranging pattern of individuals. We collected 33 urine samples from 4 female and 5 male chimpanzees in the high exposition group (5 from juveniles, 12 from subadults, 16 from adults).…”
Section: Chimpanzees' Pesticide Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…In Kibale, ticks can be found in the nostrils of both young chimpanzees and researchers [ 31 , 32 ], highlighting the potential risk of cross-contamination between humans and chimpanzees. In the Sebitoli area, chimpanzees regularly visit surrounding gardens to feed on crops [ 96 ], a proximity that could favor the cross-transmission of pathogens as has been shown for malaria [ 97 ] and Oesophagostomum infection [ 98 ].…”
Section: Discussionmentioning
confidence: 99%